How can the training load be adjusted individually in athletes with an applied statistical approach? - Claudino, J. G.; Cronin, J. B.; Amadio, A. C.; Serrao, J. C. (Journal of Athletic Enhancement, 2016)
Individually adjusting the training load of athletes is of undeniable importance, in optimizing adaptation and performance gains, however, this individualized approach has been a challenge for coaches especially in team sports. The countermovement jump (CMJ) height has been one of the most used measurements for monitoring neuromuscular status in high performance athletes. For this, the true score is essential when monitoring an individual`s "real" performance change i.e. greater than the typical error of measurement (TEM). The purpose of the present study is to describe how the minimal individual difference (MID) can be calculated and applied by researchers and practitioners. It is important that the athlete is familiarized with the countermovement jump (CMJ) as the desired outcome is for the athlete to achieve equivalency in CMJ height scores over two days. As a result of the familiarization process the TEM associated with the CMJ is reduced. For reliability testing, the athlete performs 8 CMJs each day and with this data, the MID is calculated via an excel spreadsheet. The average of the 8 jumps of the second day of reliability testing is considered as the participant`s baseline. Thus, researchers and practitioners can use the MID of CMJ to monitor neuromuscular status and regulate individual training loads.